Evaluating First Aid Skills among University Students after the Corona Crisis - Al-Jarah, Reem A.; Mohammed, Anhar K.; Al-Taee, Faris G. (PROSPECTIVE RESEARCHES, 2025)
The research aims to assess the reality of university students' knowledge of first aid and their skill levels, especially in light of the conditions that society experienced during the COVID-19 crisis. It is evident that everyone now needs to know how to handle health emergencies for themselves or their relatives. The researchers pose questions such as: What is the level of students' knowledge of first aid and the methods of providing it? Are there statistically significant differences in students' knowledge of first aid attributable to the research's demographic variables? The researchers employed the descriptive statistical method, as it aligns with the research's objectives. The research population included university students in Mosul, both from public universities (University of Mosul and Nineveh University) and private universities (Al-Hadba University and Al-Noor University), covering humanities, sciences, and medical disciplines. The number of valid responses from the questionnaire was 3,120 students. The questionnaire consisted of three main sections: general knowledge, understanding of the human body, and dealing with injuries. The research concluded with findings and recommendations for each section of the questionnaire.